PENGARUH ANGGARAN KAS, MODAL KERJA, DAN FINANCIAL LEVERAGE TERHADAP PENDAPATAN USAHA (Studi Kasus pada UMKM di Kecamatan Buleleng): Studi Kasus pada UMKM di Kecamatan Buleleng - I Gst Ayu Agung Ari Pradnyan Sinta Dewi; I Gede Putu Banu Astawa (Vokasi : Jurnal Riset Akuntansi, 2024)
This research aims to determine the effect of cash budget, working capital and financial leverage on MSME business income in Buleleng District. The research that will be used in this research is quantitative research. Data collection was carried out by distributing questionnaires and then the data was processed using the SPSS application. The collected data will be tested using descriptive statistical analysis, instrument testing, classical assumption testing and hypothesis testing. The total number of respondents was 240 MSMEs in the trade sector in Buleleng District. The research results showed that (1) Cash Budget (X1) obtained a significant probability value of t of 0.000, which means it was smaller than 0.05 and B had a positive sign of 0.734. So the cash budget variable has a positive and significant effect on MSME business income. (2) Working Capital (X2) obtained a significance probability value of t of 0.001, which means it is smaller than 0.05 and B has a positive sign of 0.317, which means that working capital has an effect on MSME business income. (3) Financial Leverage (X3) obtained a significance probability value of t of 0.000, which means it is smaller than 0.05 and B has a positive sign of 0.366, which means financial leverage has a positive and significant influence on MSME business income.